MICROENCAPSULATION OF PROBIOTIC CULTURES: PRINCIPLES OF SPRAY DRYING METHOD - Nunes, Graciele Lorenzoni (2015)
Probiotic microorganisms are known to provide a number of benefits to consumer health, primarily through the maintenance of balance and composition of the gastrointestinal tract. However, for the health benefits to be achieved, should remain viable probiotics in sufficient quantity in the food until the time of consumption, in addition to being able to survive passage through the gastrointestinal tract. Due to these factors microencapsulation methods have been applied in order to protect probiotics against adverse conditions they are exposed, improving their survival. The technique of spray drying is one commonly used for encapsulation of food ingredients, it offers some advantages, such as relatively low cost, ease of operation, high production rates and possibility of application in industrial scale. In this context, the aim of this work is to provide an overview of the importance and benefits of microencapsulation of probiotic cultures emphasizing the principles of métodode spray drying.